2021
DOI: 10.3389/fmed.2021.709712
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Action of Perfluorohexyloctane Eye Drops to Reduce Ocular Discomfort and Pain

Abstract: Perfluorohexyloctane (F6H8) eyedrops have been recently introduced in Europe as a product to treat dry eye disease, based on its ability to reduce tear film instability in Meibomian gland dysfunction and evaporative dry eye disease, although its mechanism of action is still unknown. In the present pilot study, we evaluated the effects of the ocular instillation of a single drop of commercial F6H8 eyedrops in 20 healthy humans (9 women/11 men), measuring: (a) Corneal surface temperature (CST) from infrared vide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…We demonstrated higher repeatability of HOA measurements after application of F6H8 than in untreated eyes, which is in accordance with the results of previously mentioned works. Several studies have proven the efficacy of F6H8 in the treatment of dry eye symptoms [ 28 30 ]. In a preclinical trial, Agarwal et al [ 31 ] showed a beneficial effect of F6H8 by immediately fusing with the precorneal tear film and compensating for surface irregularities.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated higher repeatability of HOA measurements after application of F6H8 than in untreated eyes, which is in accordance with the results of previously mentioned works. Several studies have proven the efficacy of F6H8 in the treatment of dry eye symptoms [ 28 30 ]. In a preclinical trial, Agarwal et al [ 31 ] showed a beneficial effect of F6H8 by immediately fusing with the precorneal tear film and compensating for surface irregularities.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the efficiency of topical antibiotics [ 84 , 85 ], with the latest evidence indicating that the act is nonpersistent [ 86 ]. In the past few years, perfluorohexyloctane has gained popularity and been widely used in developed countries as an alternative therapy for MGD-EDE [ 87 , 88 , 89 ]. The possible pharmacological mechanism is that it can serve as a surfactant, forming monolayers at the water/air interphase and preventing the evaporation of the tear film [ 89 ].…”
Section: Prospective Future Research and Therapeutic Strategiesmentioning
confidence: 99%
“…In the past few years, perfluorohexyloctane has gained popularity and been widely used in developed countries as an alternative therapy for MGD-EDE [ 87 , 88 , 89 ]. The possible pharmacological mechanism is that it can serve as a surfactant, forming monolayers at the water/air interphase and preventing the evaporation of the tear film [ 89 ]. AZR-MD-001 is currently being studied to evaluate the safety, efficacy, and tolerability in patients with MGD.…”
Section: Prospective Future Research and Therapeutic Strategiesmentioning
confidence: 99%
“…Perfluorohexyloctane is thought to create an occlusion layer and reduce eyelid shear force upon blinking, thereby avoiding the increase in vaporization resulting in DED, as it increased tear film breakup time and lipid layer thickening in patients with DED [99]. It has also been shown to provide a long-lasting cooling effect on the ocular surface [100].…”
Section: Perfluorohexyloctane Ophthalmic Solutionmentioning
confidence: 99%